2016
DOI: 10.1016/j.conbuildmat.2015.11.045
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the compressive strength of fly ash based geopolymers

Abstract: Several factors affecting the reactivity of fly ash (FA) as a precursor for geopolymer concrete have been investigated. These include physical and chemical properties of various FA sources, inclusion of ground granulated blast furnace slag (ggbs), chemical activator dosages and curing temperature. Alkali-activated FA was found to require elevated curing temperatures and high alkali concentrations. A mixture of sodium hydroxide and sodium silicate was used and this was shown to result in high strengths, as high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(88 citation statements)
references
References 29 publications
5
65
0
6
Order By: Relevance
“…It can be attributed to the hydration of Ca species and the creation of a calcium-aluminum-silicate-hydrate (C-A-S-H) gel at very rapid pace, often resulting in a very short initial setting time during the early stage of geopolymeric reaction. 45 Other researchers also indicate that excessive silicate from higher molar ratio of SiO 2 /Na 2 O may inhibit the geopolymerization due to the formation of aluminosilicate gel precipitation and further apart the aluminosilicate source and the alkali activators. [46][47][48][49][50] As shown in Figure 5b, the flexural strength of all three specimens tested increased as the curing time increased from 7 to 28 days.…”
Section: Mechanical Strength Of Geopolymer Pastementioning
confidence: 99%
“…It can be attributed to the hydration of Ca species and the creation of a calcium-aluminum-silicate-hydrate (C-A-S-H) gel at very rapid pace, often resulting in a very short initial setting time during the early stage of geopolymeric reaction. 45 Other researchers also indicate that excessive silicate from higher molar ratio of SiO 2 /Na 2 O may inhibit the geopolymerization due to the formation of aluminosilicate gel precipitation and further apart the aluminosilicate source and the alkali activators. [46][47][48][49][50] As shown in Figure 5b, the flexural strength of all three specimens tested increased as the curing time increased from 7 to 28 days.…”
Section: Mechanical Strength Of Geopolymer Pastementioning
confidence: 99%
“…As the definition currently stands [40,42], there is a wide range of potential precursors and activators that may be used and which would produce geopolymers of varying quality. In terms of the precursor, the most common candidates are high purity kaolin [43,44] and different types of clays [45][46][47], or waste/by-product materials, such as slags [40] and ashes [40,[48][49][50]. However, some of these materials may not be readily available across the globe or are too expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on pure FA AAMs (paste [30], mortar [31][32][33] or concrete [34]) indicated that FA geopolymer presents low reactivity compared with MK geopolymer and a thermal treatment is usually necessary to achieve reasonable properties (setting time and early age mechanical properties) [33]. Under ambient conditions, pure FA AAMs initial setting time is very long (more than 24 h) because of the low reactivity of the FA but good mechanical properties can be achieved if the FA AAMs are thermally cured [30,32,34].…”
Section: Introductionmentioning
confidence: 99%